2022
DOI: 10.55519/jamc-03-10305
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir Efficacy and Safety for the Treatment of Severe Coronavirus 2019. A Retrospective Study.

Abstract: Background: Corona virus disease is caused by the enveloped, single stranded RNA virus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) becoming the deadliest disease of the century. Its global outbreak has led researchers to develop drugs or vaccines to prevent the spread of the disease. Favipiravir is an approved orally administered antiviral drug that selectively inhibits RNA-dependent RNA polymerase, used off-label to treat COVID-19. Objectives: The purpose of this study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Favipiravir has been recommended and was widely used as a treatment for COVID-19 in some countries, including Thailand ( https://ddc.moph.go.th/viralpneumonia/eng/file/guidelines/g_treatment.pdf ). Although some observational studies have suggested benefit from favipiravir [ 10 14 ], and a large clinical benefit was reported in one open-label randomised controlled trial (with shortening of time to clinical improvement from 14 to 2 days in hospitalised patients) [ 15 ], the other reported randomised trials have either shown no benefit, or the evidence of clinical efficacy has been marginal or unconvincing [ 16 29 ]. However, several of these studies were conducted in hospitalised patients, in whom the window of opportunity for antivirals to benefit may have closed.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir has been recommended and was widely used as a treatment for COVID-19 in some countries, including Thailand ( https://ddc.moph.go.th/viralpneumonia/eng/file/guidelines/g_treatment.pdf ). Although some observational studies have suggested benefit from favipiravir [ 10 14 ], and a large clinical benefit was reported in one open-label randomised controlled trial (with shortening of time to clinical improvement from 14 to 2 days in hospitalised patients) [ 15 ], the other reported randomised trials have either shown no benefit, or the evidence of clinical efficacy has been marginal or unconvincing [ 16 29 ]. However, several of these studies were conducted in hospitalised patients, in whom the window of opportunity for antivirals to benefit may have closed.…”
Section: Introductionmentioning
confidence: 99%
“…Favipiravir has been recommended, and was widely used as a treatment for COVID-19 in some countries, including Thailand (10). Although some observational studies have suggested bene t from favipiravir (11)(12)(13)(14)(15), and a large clinical bene t was reported in one open-label randomised controlled trial (shortening of time to clinical improvement from 14 to 2 days in hospitalised patients) (16), the other reported randomised trials have either shown no bene t, or the evidence of clinical e cacy has been marginal or unconvincing (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, several of these studies were conducted in hospitalised patients in whom the window of opportunity for antivirals to bene t may have closed.…”
Section: Introductionmentioning
confidence: 99%